(untitled) (Deutscher Suchtkongress, 2023)
Refugees are at high risk of mental health problems due to their pre-migration experiences, war, and post-migration challenges. Although recent studies also shed light on substance use disorders (SUDs) as another risk to refugees’ mental health, our understanding of SUDs among diverse ethnic refugee groups is still limited. This plenary aims at comprehending the topic from a holistic overview as perceived by practitioners and refugees from different countries over a decade. The data presented in this plenary is based on two studies: (1) a systematic review of qualitative research, and (2) an in-depth qualitative study conducted among Arabic-speaking refugees in Germany. The evidence synthesis of several studies conducted in host countries, such as the U.S., Australia, and Germany, revealed that refugees are at considerable susceptibility to SUDs, and their social insecurities complicate the harmful consequences of substance use. Refugees are struggling with complex barriers to treatment in many host countries, and improving effective access to treatment, interventions and prevention approaches is strongly needed. Although refugees are often treated as a universal group, their perspectives vary based on their diverse sociocultural backgrounds; understanding SUDs (a sociocultural and legally sensitive topic) is a significant challenge in host countries. Further in-depth studies are required to inform practitioners and policymakers in the clinical and social institutions.